2019
DOI: 10.1002/ajmg.a.61389
|View full text |Cite
|
Sign up to set email alerts
|

Brain white matter abnormalities associated with copy number variants

Abstract: White matter (WM) signal abnormalities are demonstrated in various neurodevelopmental disorders on brain magnetic resonance imaging (MRI). The pattern of WM abnormalities can aid in the diagnostic process. This study aims to characterize the WM changes found in microdeletion/microduplication syndromes. Thirteen patients with neurodevelopmental disorders due to copy number variations were collected from a cohort of children with evidence of WM abnormalities on brain MRI, in two medical centers. A pediatric neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Brain MRI showed defective white matter myelination for age in our proband. This finding is consistent with Vigdorovich et al [2020] who emphasized that micro-rearrangement syndromes including 1p36 deletion syndrome should be considered in patients with delayed myelination or hypomyelination of white matter. Although monosomy 1p36 is a clinically recognizable syndrome, phenotypic differences are frequently detected between patients.…”
Section: Discussionsupporting
confidence: 89%
“…Brain MRI showed defective white matter myelination for age in our proband. This finding is consistent with Vigdorovich et al [2020] who emphasized that micro-rearrangement syndromes including 1p36 deletion syndrome should be considered in patients with delayed myelination or hypomyelination of white matter. Although monosomy 1p36 is a clinically recognizable syndrome, phenotypic differences are frequently detected between patients.…”
Section: Discussionsupporting
confidence: 89%
“…We now know that brain images that mimic HIE can be seen in some microdeletion/microduplication disorders. 3 All the microdeletions and microduplications (only studied since 2005), as well as the chromosome abnormalities listed in Table 1, were found after the birth of a child with claimed HIE. Parental microarrays were mostly not carried out, and the significance of deletions/duplications often not proven because of legal strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Determination of deletion or duplication in patients with CNV increased the risk of myelination disorders 4.77-fold compared to the normal group. Vigdorovich et al (37), also determined that different chromosomal micro-rearrangement syndromes create nonspecific multifocal and especially periventricular white matter changes as a common feature at CMRI. The authors also reported that these lesions may also be accompanied by corpus callosum dysgenesis or gray matter loss.…”
Section: Discussionmentioning
confidence: 99%